Affective dimensions of teaching and doing development. (15th July 2018) - Tschakert, Petra; Henrique, Karen Paiva; Bitmead, Robert; Dassu, Fahima; Crowther, Michelle; Yukhnevich, Zoya; Anderson, Christopher; Roddy, Abby; Bye, Veronica; Rawlinson, Akheam; O'Hara, Nicola; Mottershead, Amanda; et al.
Abstract : Like the development industry, development pedagogy and practice have begun to take into account the role of emotions and the deeper, affective and embodied experiences of understanding and doing development. In her ground‐breaking piece 'Emotional geographies of development', Sarah Wright illustrates how emotions not only create development subjects and associated subjectivities, but also provide a powerful entry point for resistance that may ultimately lead to transformative social change. Post‐colonial and feminist scholars have long emphasised the role of emotions such as anger, fear, shame, joy and hope in discursive construction of the 'Other' and the persistence of false binaries that obscure layers of struggle, exclusion and disenfranchisement. In this paper, we (students and educators) reflect on the role of emotions and affective engagements with development, drawing upon classroom discussions as well as reading and reflection logs of those studying for a Master in International Development (MID) at the University of Western Australia. We explore how explicit efforts to be attentive to our own emotions while digesting and deliberating material for this unit allow us to better grasp our own positionality while revisiting our personal entanglements with the 'Other' – the quintessential development subject. Making space for 'more‐than‐rational' aspects of development enables scholars and educators to experiment with affective options for interdisciplinary teaching in a distinctly more personal way than students may expect from a postgraduate degree in international development.